Biomechanics of Transforaminal Endoscopic Approaches. Issue 24 (15th December 2022) - Farshad, Mazda; Hagel, Vincent; Spirig, José M.; Fasser, Marie-Rosa; Widmer, Jonas; Burkhard, Marco D.; Calek, Anna-Katharina
Abstract : Study Design: Biomechanical cadaveric study. Objective: The aim of this study was to compare the effect of transforaminal endoscopic approaches with open decompression procedures. Summary of Background Data: Clinical studies have repeatedly highlighted the benefits of endoscopic decompression, however, the biomechanical effects of endoscopic approaches (with and without injury to the disk) have not been studied up to now. Materials and Methods: Twelve spinal segments originating from four fresh-frozen cadavers were biomechanically tested in a load-controlled endoscopic transforaminal approach study. Segmental range of motion (ROM) after endoscopic approach was compared with segmental ROM after (1) microsurgical decompression with unilateral laminotomy and (2) midline decompression with bilateral laminotomy. In the intact state and after decompression, the segments were loaded in flexion-extension (FE), lateral shear (LS), lateral bending (LB), anterior shear (AS), and axial rotation (AR). Results: Vertebral segment ROM was comparable between the two endoscopic transforaminal approaches. However, there was a—statistically nonsignificant—trend for a larger ROM after accessing via the inside-out technique: FE: +3% versus +7%, P =0.484; LS: +1% versus +12%, P =0.18; LB: +0.6% versus +9%, P =0.18; AS: +2% versus +11%, P =0.31; AR: −4% versus +5%, P =0.18. No significant difference in vertebral segment ROM was seen between the transforaminal endoscopic approaches and open unilateral decompression. Vertebral segment ROM was significantly smaller with the transforaminal endoscopic approaches compared with midline decompression for almost all loading scenarios: FE: +4% versus +17%, P =0.005; AS: +6% versus 21%, P =0.007; AR: 0% versus +24%, P =0.002. Conclusion: The transforaminal endoscopic intracanal technique preserves the native ROM of lumbar vertebral segments and shows a trend toward relative biomechanical superiority over the inside-out technique and open decompression procedures.